2014
DOI: 10.4097/kjae.2014.67.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the ability of continuous palonosetron infusion, using a patient-controlled analgesia device, to reduce postoperative nausea and vomiting

Abstract: BackgroundThe efficacy of palonosetron in preventing postoperative nausea and vomiting (PONV), as well as chemotherapy-induced nausea and vomiting, has already been demonstrated in multiple clinical studies. The purpose of this study was to determine whether continuous infusion of palonosetron following single injection could reduce PONV to a greater extent than single injection only of palonosetron.MethodsIn total, 132 women were enrolled in the study. All subjects were over the age of 20 years and were sched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Palonosetron is the latest serotonin receptor antagonist ( 3 , 6 – 8 , 13 , 16 , 17 ). Serotonin is an ubiquitous central and peripheral neurotransmitter thought to be the predominant mediator of the perception of nausea and triggering of the vomiting response ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palonosetron is the latest serotonin receptor antagonist ( 3 , 6 – 8 , 13 , 16 , 17 ). Serotonin is an ubiquitous central and peripheral neurotransmitter thought to be the predominant mediator of the perception of nausea and triggering of the vomiting response ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…This occurs in both the brain and the periphery via the serotonin 5-hydroxytryptamine type 3 [5-HT(3)] receptor pathways ( 19 ). Palonosetron, compared to older 5-HT3 receptor antagonist, such as ondansetron, granisetron, dolasetron, and ramosetron, has higher receptor binding affinity and longer plasma half-life (40 h) ( 3 , 6 – 8 , 13 , 16 , 17 ). The most effective dose for PONV is a single 0.075 mg IV dose administered over 10 s right before anesthesia induction ( 5 , 6 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two previous studies compared the prophylactic antiemetic effects of the continuous infusion of ondansetron and palonosetron following the single bolus administration of antiemetics and concluded that the continuous infusion of the antiemetics reduced the PONV incidence compared with the placebo infusion group [14,15]. However, the studies were designed that the total doses of antiemetics were different, unlike the present study, between the placebo and antiemetic infusion groups.…”
Section: Resultsmentioning
confidence: 54%